RETROSPECTIVE ANALYSIS OF FORMATION OF INSTRUMENTAL APPROACH TO DECEPTION DETECTION - Малюга, В.; Кравченко, А.; Зубовський, Д. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article contains a retrospective analysis of formation of instrumental approach to deception detection. The article reveals the history of formation and development containing a lot of moments of scientific thought fluctuations. Article deals with the key theoretical and practical achievements of scientists who laid the foundation for modern methodology of the survey using polygraph. Keywords: deception, polygraph, retrospective analysis, associative experiment, a survey using polygraph.